Associations between osteoporosis and exposure to air pollution: results from a cross-sectional study on 45,483 adults in Italy - Bianconi, Alessandro; Angeletti, Edoardo; Fiore, Matteo; Gori, Davide; Guaraldi, Federica; Lenzi, Jacopo; Sanmarchi, Francesco (Acta Biomedica Atenei Parmensis, 2024)
Background and aim of the work: Osteoporosis is a disease characterized by the chronic deterioration of bone tissue, leading to an increased risk of fractures, hospitalization and mortality. Recent studies highlighted that exposure to air pollution may represent a risk factor for osteoporosis. This study aimed to investigate the association between air pollution exposure and osteoporosis in a sample of 45,483 Italian adults.Research design and Methods: Osteoporosis Data were extracted from a nationwide survey conducted by the Italian National Institute of Statistics in 2019. A logistic regression model was employed to analyze the association between osteoporosis and self-reported levels of air pollution in residential areas. The model was adjusted by sociodemographic characteristics, comorbidities, and lifestyle factors. The Benjamini–Hochberg procedure was applied to multiple comparisons occurring in multivariable analysis to control the false discovery rate. Gender stratified analyses were also performed.Results: Higher odds of osteoporosis were found in individuals living in areas reported as ‘very polluted' (OR = 1.35, 95%CI = 1.17–1.57, q